Risk Factors Responsible for the High-Risk Pregnancy and Its Association with the Outcome of the Pregnancy among the High-Risk Mothers of Bhavnagar District, Gujarat: A Follow-Up Descriptive Study - Chauhan, Pooja A; Bhalani, K. D.; Trivedi, Atul (National Journal of Community Medicine, 2019)
Background: According to WHO, globally about 830 women die from pregnancy or childbirth-related complications every day. About 20-30% of all pregnancies belong to high-risk category, which is responsible for 70–80% of perinatal mortality and morbid- ity. Objectives: This study was conducted to analyze the distribution of the risk factors responsible for the high-risk pregnancy and its association with the outcome of pregnancy among the high-risk mothers. Methods: A descriptive study was conducted among the high-risk pregnant women of Bhavnagar district registered at the PHCs of Bhavnagar district by visiting them twice (i.e. once during the third trimester and again after delivery) for conducting the inter- view. Results: Among the high-risk mothers, in the worst performing PHCs, anaemia was the most common risk factor (66.7%) followed by bad obstetric history and multiparity (31.1% each), while in the best performing PHCs also, anaemia was the most common risk factor (44.4%) followed by previous caesarean section (33.3%).In the worst performing PHCs, 60% of the high-risk mothers, while in the best performing PHCs, 44.4% of the mothers were having more than one risk factors. Conclusions: The association between the anaemia, multipara, his- tory of previous caesarean section and the mode of delivery was found statistically significant.